2018
DOI: 10.1101/501882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ASCOT identifies key regulators of neuronal subtype-specific splicing

Abstract: 1Public archives of next-generation sequencing data are growing exponentially, but the difficulty of 2 marshaling this data has led to its underutilization by scientists. Here we present ASCOT, a resource that 3 allows researchers to summarize, visualize, and query alternative splicing patterns in public RNA-Seq 4 data. ASCOT enables rapid identification of splice-variants across tens of thousands of bulk and single-5 cell RNA-Seq datasets in human and mouse. To demonstrate the utility of ASCOT, we first focus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 69 publications
(75 reference statements)
5
41
0
Order By: Relevance
“…We analyzed the expression of Musashi proteins in various tissues from adult mice. Out of all the tissues we tested, retina showed the highest expression of MSI1 and MSI2 proteins ( Figure 1A), in line with the previously reported high transcript levels for Msi1 and Msi2 in rod photoreceptors (9). Quantitative RT-PCR of Msi1 and Msi2 levels in the tissues shown on Figure 1A further confirmed significantly higher levels of expression of the two transcripts in retina ( Figure 1B).…”
Section: Validation Of the Conditional Knockout Mouse Modelssupporting
confidence: 88%
“…We analyzed the expression of Musashi proteins in various tissues from adult mice. Out of all the tissues we tested, retina showed the highest expression of MSI1 and MSI2 proteins ( Figure 1A), in line with the previously reported high transcript levels for Msi1 and Msi2 in rod photoreceptors (9). Quantitative RT-PCR of Msi1 and Msi2 levels in the tissues shown on Figure 1A further confirmed significantly higher levels of expression of the two transcripts in retina ( Figure 1B).…”
Section: Validation Of the Conditional Knockout Mouse Modelssupporting
confidence: 88%
“…We analyzed the expression of Musashi proteins in various tissues from adult mice. Out of all the tissues we tested, retina showed the highest expression of MSI1 and MSI2 proteins ( Figure 1A), in line with the previously reported high transcript levels for Msi1 and Msi2 in rod photoreceptors (9). To test the biological significance of Musashi protein expression in the murine retina, we used Cre-LoxP conditional recombination to remove either Msi1, Msi2, or both the Msi1 and Msi2 genes throughout the entire retina and ventral forebrain using the Six3 Cre transgene (26).…”
Section: Validation Of the Conditional Knockout Mouse Modelssupporting
confidence: 90%
“…In addition, Musashi promotes the splicing of several photoreceptor specific exons when over-expressed in cultured cells (8). Recently, analysis of a comprehensive gene expression data set demonstrated that photoreceptors utilize a unique set of alternative exons that are primarily regulated by MSI1 and MSI2 (9).…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify cells that show adipocyte signatures, key adipocyte-enriched genes were first extracted from GTEx dataset from ascot.cs.jhu.edu, 22 relying on both robustness (NAUC > 20) and specificity (expressed only in both adipocytes dataset or in tissues that are enriched with adipocytes, such as mammary tissues). These genes were then used to train the dataset using Garnett 23 to identify differentiated adipocytes.…”
Section: Single-nucleus Rna-seqmentioning
confidence: 99%